A Practice Perspective on Market Evolution: How Craft and Commercial Coffee Firms Expand Practices and Develop Markets. (November 2022) - Dolbec, Pierre-Yann; Arsel, Zeynep; Aboelenien, Aya
How markets evolve is a perennial and important question in business. Building on a large qualitative data set on the coffee market comprising primary and secondary interviews, archival data, and fieldwork, the authors introduce a novel theoretical mechanism—practice expansion—to explain how ongoing institutional complexity fosters market evolution. To theorize practice expansion, the authors combine institutional logics with resource partitioning and introduce a two-by-two typology of firms evolving in markets: craft versus commercial and generalist versus specialist. The authors' analysis, grounded in this typology, identifies three mechanisms that explain practice expansion (elaboration, translation, and transformation). The authors then show how practice expansion contributes to market evolution by increasing product diversity, broadening skills and knowledge, and enriching the market meaning system. The novel theory introduced in this article contributes to extant work by theorizing market evolution as resulting from practice expansion and by broadening our understanding of the types of firms and their interactions important to that evolution. The novel theory also points to important strategy implications for how different types of firms can contribute to and benefit from the identified evolutionary patterns and ongoing institutional complexity.